Peningkatan Retensi Tenaga Kesehatan di Industri Jasa Melalui Strategi Kompensasi - Maratu Solihah; Ratna Indrawati; Hasyim Hasyim (Jurnal Health Sains, 2022)
Low retention of healthcare workers may contribute to a negative impact on the performance and effectiveness of the service industry, which is caused by several major factors including compensation provided by industry that does not meet employee expectations, and there is no stipulated compensation for overtime work in the form of incentives or bonuses. Furthermore, the organizational commitment of the healthcare workers is still considered low, due to the service industry’s operations which have only been running for one year. This study intended to provide empirical evidence of the effect of compensation and motivation on retention of healthcare workers mediated by organizational commitment. This study utilized quantitative methods with the type of causality study. The data in this study were sourced from primary data.  Individual analysis subjects consisted of all healthcare workers with a service period of more than one year.  Path analysis data analysis was used in this study. The results of the study indicated that compensation, motivation and organizational commitment simultaneously had a positive and significant effect on the retention of healthcare workers with organizational commitment as an intervening variable. Furthermore, compensation and motivation partially had a positive and significant effect on organizational commitment.  Moreover, ccompensation, motivation and organizational commitment contributed to a positive and significant effect on the retention of healthcare workers. Findings of the study indicated that the direct effect of compensation and motivation on the retention of healthcare workers was greater than that mediated by organizational commitment